Clusters of prediabetes and type 2 diabetes stratify all-cause mortality in a cohort of participants Undergoing invasive coronary diagnostics - Prystupa, Katsiaryna; Delgado Gonzales de Kleber, Graciela; Moissl-Blanke, Angela P.; Kleber, Marcus E.; Heni, Martin; Birkenfeld, Andreas L.; Fritsche, Andreas; März, Winfried; Wagner, Róbert (Diabetes, 2022)
Risk for complications and mortality among patients with type 2 diabetes (T2D) is heterogenous. Different trajectories can be identified in the prediabetic state, which comprises heterogenous metabolic clusters. It is not known whether such pathophysiologic clusters of prediabetes and diabetes affect survival in at-risk persons being evaluated for coronary heart disease. The LURIC Study recruited patients referred for coronary angiography at a median age of 63 (IQR 56-70) who have since been followed-up for a median of 14.5 (IQR 9.6-17.7) years. Clustering of 1269 subjects without diabetes was performed with oGTT-derived glucose and insulin; fasting triglyceride, high-density lipoprotein, BMI, waist and hip circumference. Patients with T2D (n=794) were clustered using age, BMI, glycemia, homeostasis model assessment, and islet autoantibodies. Associations of clusters with mortality were analyzed using Cox regression. Individuals without diabetes were classified into six subphenotypes, with 884 assigned to subjects at low-risk (cluster 1,2,4) and 385 at high-risk (cluster 3,5,6) for diabetes. We found significantly increased mortality in clusters 3 (hazard ratio (HR) 1.42) , 5 (HR 1.43) and 6 (HR 1.46) age-, BMI-, HbA1c- and sex-adjusted. In the T2D group, 5were assigned to mild age-related diabetes (MARD) , 183 to severe insulin-resistant diabetes (SIRD) , 84 to mild obesity-related diabetes (MOD) , to severe insulin-deficient diabetes (SIDD) . Compared to the low-risk nondiabetes group, crude mortality was not different in MOD. An increased mortality was found for MARD (HR 2.2) , SIRD (HR 2.2) and SIDD (HR 2.5) . Metabolic clustering successfully stratifies survival even among persons already undergoing invasive coronary diagnostics. Novel clustering approaches based on glucose metabolism can identify persons who require special attention as they are in danger of increased mortalityK.Prystupa: None. G.Delgado: None. A.P.Moissl: None. M.E.Kleber: Employee; SYNLAB Holding Deutschland GmbH. M.Heni: Advisory Panel; Boehringer Ingelheim International GmbH, Research Support; Boehringer Ingelheim International GmbH, Sanofi, Speaker's Bureau; Amryt Pharma Plc, Boehringer Ingelheim International GmbH, Novo Nordisk. A.L.Birkenfeld: None. A.Fritsche: Advisory Panel; Boehringer Ingelheim International GmbH, Novo Nordisk, Sanofi-Aventis Deutschland GmbH. W.Maerz: None. R.Wagner: Advisory Panel; Akcea Therapeutics, Daiichi Sankyo, Sanofi-Aventis Deutschland GmbH, Speaker's Bureau; Lilly, Novo Nordisk, Sanofi-Aventis Deutschland GmbH.German Federal Ministry of Education and Research (BMBF) (01GI0925)
Gesehen am 12.11.2025